PENGARUH MODEL PEMBELAJARAN DIRECT INSTRUCTION TERHADAP KETERAMPILAN MENGOPERASIKAN MICROSOFT EXCEL SISWA KELAS IX SMP NEGERI 13 BALIKPAPAN - Ramadhani, Bemby; Nirawana, I Wayan Sugianta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the limited students’ skills in operating Microsoft Excel despite the integration of technology in learning. This study aims to determine whether there is an effect of the Direct Instruction learning model on students’ skills in operating Microsoft Excel. The method used is a quantitative approach with a quasi-experimental design involving ninth-grade students of SMP Negeri 13 Balikpapan. Data were collected through observation, interviews, tests, and supporting instruments. The results showed that students’ skills improved significantly after the implementation of Direct Instruction, as indicated by higher posttest scores compared to the control class and a significance value of 0.003 (< 0.05). The N-Gain results also showed a higher improvement in the experimental class. Therefore, this model is effective in improving students’ skills and psychomotor abilities through structured learning, guided practice, and independent practice.